2018
DOI: 10.1111/ppc.12272
|View full text |Cite
|
Sign up to set email alerts
|

Advanced practice registered nurses attitudes toward suicide in the 15- to 24-year-old population

Abstract: One of the outcomes of this study is to raise awareness and foster prevention related to suicide for advanced practice registered nurses and the 15- to 24-year-old population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This finding is consistent with that of [21] who indicate that casualty nurses in the middle of Taiwan held favourable attitudes towards suicide on the scale of SOQ. Also, current study support evidence from previous observations revealing positive among health care provid-Open Journal of Nursing ers towards suicide behaviour [8] [12] [16]. For instance, [8] demonstrate that nurses and doctors held positive attitudes towards patient who had attempted suicide.…”
Section: Interpretation Of the Study Findings: Links To Existing Rese...supporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with that of [21] who indicate that casualty nurses in the middle of Taiwan held favourable attitudes towards suicide on the scale of SOQ. Also, current study support evidence from previous observations revealing positive among health care provid-Open Journal of Nursing ers towards suicide behaviour [8] [12] [16]. For instance, [8] demonstrate that nurses and doctors held positive attitudes towards patient who had attempted suicide.…”
Section: Interpretation Of the Study Findings: Links To Existing Rese...supporting
confidence: 88%
“…In contrast, uncertain attitudes toward suicide and suicide attempters amongst nursing students were detected [15]. In regard to nurses, a study conducted by [16], revealed that paediatric nurses have more favourable attitudes towards suicide and suicidal attempters compared with psychiatric nurses in the USA.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Sampling and data collection protocol We surveyed homeowners and tenants (included for the first time in such a study as a control group) of Ottawa and Gatineau census metropolitan area (CMA) who met the following criteria: resident in a house with a basement or a house in contact with the ground for over one year. Participants were randomly selected from the residents' panel with Qualtrics, a platform frequently used in standard research studies (Farris et al 2018;Glodstein et al 2018). Participants received email invitations, along with a link to the online survey in both French and English.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, it is important to identify and implement effective responses. The literature indicates that suicide interventions require improvement, 24,27 and consideration is needed regarding ways to enhance readiness to respond to people at risk of suicide and self‐harm 6,28 . In any case, to manage risk and safeguard staff, it was suggested that one nominated evidence‐based psychosocial assessment should be utilized, to ensure comprehensive assessment and uniformity of practice, while also taking into account individual need.…”
Section: Discussionmentioning
confidence: 99%